2015
DOI: 10.1080/14681811.2015.1057635
|View full text |Cite
|
Sign up to set email alerts
|

Sense about sex: media, sex advice, education and learning

Abstract: The media are widely acknowledged as important in sex and relationship education, but they are usually associated with 'bad' effects on young people in contrast to the 'good' knowledge represented by more informational and educational formats. In this paper we look at sex advice giving in newspapers, magazines and television in the UK, in sex advice books and in online spaces for sexual learning. We examine some of the limitations of the information provided, consider the challenges for sex advice in the conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 39 publications
1
64
0
1
Order By: Relevance
“…With the exception of sexual orientation (Charest, Kleinplatz, & Lund, 2016;Mitchell et al, 2014), other variables that relate to youth's intrinsic needs and motivations, such as sexual curiosity, need for sexual information (for instance about sexual problems) and sexual (self-) views, have not yet been investigated in relation to online sexual information seeking. Moreover, it has also been suggested that youth turn online for sexuality education when the messages that they receive from offline sources (i.e., parents and schools) are not tailored to their personal needs and preferences (Attwood et al, 2015;Doornwaard et al, 2017;McKee, 2012), but empirical research on the role of such extrinsic factors is scarce and mostly qualitative in nature (McKee, 2012). As a result, we do not know to what extent online sexual information seeking is predicted by intrinsic factors and/or extrinsic factors.…”
Section: Online Sexual Self-socializationmentioning
confidence: 98%
“…With the exception of sexual orientation (Charest, Kleinplatz, & Lund, 2016;Mitchell et al, 2014), other variables that relate to youth's intrinsic needs and motivations, such as sexual curiosity, need for sexual information (for instance about sexual problems) and sexual (self-) views, have not yet been investigated in relation to online sexual information seeking. Moreover, it has also been suggested that youth turn online for sexuality education when the messages that they receive from offline sources (i.e., parents and schools) are not tailored to their personal needs and preferences (Attwood et al, 2015;Doornwaard et al, 2017;McKee, 2012), but empirical research on the role of such extrinsic factors is scarce and mostly qualitative in nature (McKee, 2012). As a result, we do not know to what extent online sexual information seeking is predicted by intrinsic factors and/or extrinsic factors.…”
Section: Online Sexual Self-socializationmentioning
confidence: 98%
“…Nowadays the media and peers have become more important sources for young people's information on sexuality issues (Darabi et al 2008;Munthali and Zulu 2007). Although these information sources can be valuable, their quality can be inconsistent or poor, and they can provide conflicting messages and problematic representations of sex (Attwood et al 2015;Cheetham 2014; UNESCO, UNAIDS, UNFPA, UNICEF, and WHO 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Much work on sex education has shown how the media create and reinforce discourses around sexuality which tend to be conservative, judgmental and shaming (Attwood et al, 2015: 529). Research on magazines shows that they reinforce oppressive notions of femininity and influence what is considered normative sexual practice (Bachechi and Hall, 2015; Farvid and Braun, 2014; McRobbie, 1996; Reviere and Byerly, 2013).…”
Section: Sex Education Discourses In Magazinesmentioning
confidence: 99%
“…These traditional discourses include ‘compulsory heterosexuality’, whereby heterosexuality is explicitly privileged over other forms of sexuality (Fine, 1998; Rich, 1980: 632). Alternative sexualities are problematised, minimised, absent or treated as ‘deviant’, except in the case of resources specifically targeted at queer audiences (Attwood et al, 2015; Clarke, 2009; Jackson, 2005a; Kehily, 1999b). There is an overwhelming focus on pregnancy, involving the assumption that sex is equivalent to penile–vaginal intercourse.…”
Section: Sex Education Discourses In Magazinesmentioning
confidence: 99%